Star Wars : in the shadow of Yavin. Volume one - Wood, Brian, 1972- (Spotlight, a division of ABDO, 2015)
"The Rebel Alliance saw victory at the Battle of Yavin, yet is fledgling. It needs supplies, allies, and a new base. Princess Leia, Luke Skywalker, and Han Solo continue their quest for a new home"--Provided by publisher.